THE ANALYSIS OF WORD FORMATION PROCESS ON MADURESE LANGUAGE - Dinar Vincy Yunitaka B; Zainollah (Kariman: Jurnal Pendidikan Keislaman, 2022)
The reason of the researcher taking this tittle is because one of the efforts to maintain and preserve Madurese language as the mother tongue of Madurese people to study continuously in all circles and levels by using Madurese language either in formal or non-formal events. In this research, the researcher used descriptive qualitative research to know more about word formation process and describes how word formation process on Madurese language used by millennial community at Kebunan Bugih Pamekasan. The data is taken from daily talking and expression by using observation, interview, and documentation. The data were collected then analyzed through familiarizing and organizing, coding and reducing, and interpreting and representing. Based on data collected, the researcher found 48 words used by millennial community at Kebunan Bugih Pamekasan in daily talking and expression that included to word formation process. The researcher concluded that the 48 words of Madurese language used by millennial community at Kebunan Bugih Pamekasan are devided into: 6 words of compounding, 4 words of blending, 18 words of clipping, 7 words of derivition, 5 words of multiple processes, and 10 words of reduplication. The researcher hopes that this research will give valuable information for the readers include word formation process on Madurese language.